2007
DOI: 10.1007/s11239-007-0169-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hypercoagulability markers and lipid levels in postmenopausal women undergoing either oral or transdermal hormone replacement therapy

Abstract: After 3 months of oral HRT and in the absence of major genetic and acquired risk factors, women displayed a predisposition for activation of blood coagulation, and an increased activity of the fibrinolytic system. Oral HRT seemed to be more effective in predisposing haemostatic changes as compared to transdermal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Estrogen and progestogen are administered in hormone replacement therapy (HRT) to postmenopausal women with the purpose of preventing the symptoms of menopause, such as hot flashes, nocturnal sweat, mood swings, insomnia, palpitation, atrophy of urogenital system, higher risk of ischemic heart disease, osteoporosis, insulin-resistance, and atherosclerosis (Callejon et al, 2005;Guimarães et al, 2009). HRT should be individually adjusted-"tailored hormonal therapy".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogen and progestogen are administered in hormone replacement therapy (HRT) to postmenopausal women with the purpose of preventing the symptoms of menopause, such as hot flashes, nocturnal sweat, mood swings, insomnia, palpitation, atrophy of urogenital system, higher risk of ischemic heart disease, osteoporosis, insulin-resistance, and atherosclerosis (Callejon et al, 2005;Guimarães et al, 2009). HRT should be individually adjusted-"tailored hormonal therapy".…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HRT brings 2-4-fold risk of venous thromboembolism (VTE) which includes deep vein thrombosis, pulmonary embolism, and stroke. The risk of VTE is higher in the first 6-12 months of HRT and gradually decreases over several years (Peverill, 2003;Gomes and Deitcher, 2004;Guimarães et al, 2009;Stevenson, 2009). This increased risk of VTE may occur due to the activation of coagulation or inhibition of fibrinolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of PAI-1:Ag were found in women who used transdermal postmenopausal hormonal therapy than in those who received oral postmenopausal hormonal therapy. Other studies [30][31][32][33][34][35][36] demonstrated that oral postmenopausal hormonal therapy signi cantly reduced the levels of PAI-1 (by up to 50%); however, no such signi cant change was associated with transdermal postmenopausal hormonal therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of studies have reported con icting results regarding brinolytic activity in human and rats [27][28][29][30][31][32][33][34][35][36]. Additionally, no report on the in uence of norethisterone acetate and drospirenone on the tPA and PAI-1 levels in liver and brain tissue of rats has been published to date.…”
Section: Discussionmentioning
confidence: 99%
“…The increased rate of cardiovascular incidents was found in hiperfibrinogenemia, which is connected with other risk factors, such as advanced age, postmenopausal state, inflammation processes, hypertension, diabetes mellitus and dyslipidemia [ 7,8].…”
Section: Introductionmentioning
confidence: 99%